KETERAWETAN LIMA JENIS ROTAN KOMERSIL TERHADAP BAHAN PENGAWET DAUN MANGROVE (Sonneratia Alba) - zakiah uslinawaty; Pujirahayu Pujirahayu; Nurhayati Nurhayati; Abigael Kabe; Nurnaningsih Hamzah (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
This study aims to determine the durability of five types of commercial rattan is rattan batang, lambang, noko, tohiti and cacing against mangrove leaf extract ( Sonneratia alba ). This type of research uses the descriptive method. In this study the concentration of the mangrove leaf ( Sonneratia alba ) preservative solution used was 4%. Each type of rattan underwent 3 trials with immersion time of 3 days and 6 days and the average value was calculated. The total of all experiments is 30 experimental units. The results showed that the type of rattan that was preserved affected the values obtained in the absorption of preservatives, retention and penetration values. The highest absorption value was found in the type of worm rattan with an achievement of 348.0 kg/m3, the highest retention value was found in the type of worm rattan with an acquisition of 41.8 kg/m3. Meanwhile, the highest penetration value was found in Tohiti rattan with a gain of 11.78 mm.